An RNA aptamer restores defective bone growth in FGFR3-related skeletal dysplasia in mice - Kimura, Takeshi; Bosakova, Michaela; Nonaka, Yosuke; Hruba, Eva; Yasuda, Kie; Futakawa, Satoshi; Kubota, Takuo; Fafilek, Bohumil; Gregor, Tomas; Abraham, Sara P; Gomolkova, Regina; Belaskova, Silvie; et al. (Science translational medicine, 2021)
Achondroplasia is the most prevalent genetic form of dwarfism in humans and is caused by activating mutations in FGFR3 tyrosine kinase. The clinical need for a safe and effective inhibitor of FGFR3 is unmet, leaving achondroplasia currently incurable. Here, we evaluated RBM-007, an RNA aptamer previously developed to neutralize the FGFR3 ligand FGF2, for its activity against FGFR3. In cultured rat chondrocytes or mouse embryonal tibia organ culture, RBM-007 rescued the proliferation arrest, degradation of cartilaginous extracellular matrix, premature senescence, and impaired hypertrophic differentiation induced by FGFR3 signaling. In cartilage xenografts derived from induced pluripotent stem cells from individuals with achondroplasia, RBM-007 rescued impaired chondrocyte differentiation and maturation. When delivered by subcutaneous injection, RBM-007 restored defective skeletal growth in a mouse model of achondroplasia. We thus demonstrate a ligand-trap concept of targeting the cartilage FGFR3 and delineate a potential therapeutic approach for achondroplasia and other FGFR3-related skeletal dysplasias.
Keywords: krysa rodu Rattus; Animals; achondroplazie; Aptamers, Nucleotide; chondrocyty; Cell Differentiation; buněčná diferenciace; Rats; Receptor, Fibroblast Growth Factor, Type 3; zvířata; receptor fibroblastových růstových faktorů, typ 3; aptamery nukleotidové; Mice; Bone Development; Achondroplasia; Chondrocytes; vývoj kostí; myši